Macro and microscopic comparison of the upper pole of the spleen with the lower pole in partial splenectomy - Paulo,Lucas Nagib Lemos (2020)
Abstract Purpose To evaluate the viability of the upper (UP) and lower pole (LP) of the spleen from a macro and microscopic point of view, after subtotal splenectomy with preservation (SSP) of the UP and the LP. Methods Seventeen male Wistar rats, two months old, were submitted to SSPUP and SSPLP and 5 to simulated operation (SG). After 80 days, the rats were euthanized, and the remaining LP and UP and intact spleens were evaluated macroscopically and microscopically. Results Two rats died during the operation. Macroscopic analysis showed that in 15 LP, one of them was not viable and in 15 UP and in 5 spleens in the SG, all were viable. In the statistical analysis, there was no difference in relation to viability. The LP and UP analyzed showed variation. As for the length, the UP increased significantly; however, in relation to the width, there was a significant increase in the LP in relation to the UP. In addition, the weight of the UP was significantly greater than that of the LP. Microscopic analysis attested viability of the splenic remnants. Conclusion There was no significant difference regarding the viability of UP and LP, in macroscopy and microscopy.